PENELUSURAN RENDAHNYA TINGKAT VAKSIN DAN UPAYA MENINGKATKAN KETERCAPAIAN VAKSINASI COVID-19 DI DESA JADA BAHRIN, KABUPATEN BANGKA - Fajar Indah Puspita Sari; Anisa Indriawati; Kamalia Layal; Salmi Salmi (Fakultas Teknik, Universitas Bangka Belitung, 2022)
Jada Bahrin village has an area of 56 km2, and consists of 3 hamlets. The boundaries of Jada Bahrin Village are, among others, in the north by Kimak Village, in the south by Balun Ijuk, in the west by Kemuja and in the east by Baturusa village. The majority of Jada Bahrin's livelihood is farming (80%). During the 2020-2021 pandemic, the Jada Bahrin village community was classified as having quite low awareness in the implementation of the Covid-19 Vaccination, until March 2022 the achievement rate of vaccine dose 1 was only 60% and dose 2 vaccine was only 40%. Seeing some of the existing problems, the team took several steps to help the community and village officials to overcome these problems. Some of the things that the service team did were collecting data on the number of people who had vaccinated and had not vaccinated, education was carried out through several points of view, namely from the point of view of medicine and science, education about hypertension, health consultation assistance and health screening. The search results from 84 communities showed that up to mid-July 2022, 15.5% of the people had not / did not vaccinate. 69.23% of them are not eligible for the vaccine because of illness.